2000
DOI: 10.1016/s0925-4439(00)00010-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel human member of the DEAD box protein family

Abstract: The cDNA library of human pancreatic islets was screened with sera from patients with insulin-dependent diabetes mellitus (IDDM). From the library screening, we isolated a novel cDNA, RNA helicase-like protein (RHELP), which exhibited strong sequence homology to p68 RNA helicase, a prototypic member of the DEAD (Asp-Glu-Ala-Asp) box protein family. Sequence analysis of the cDNA revealed that RHELP contained DEAD sequence motif and other conserved motifs of the DEAD box protein family, indicating that RHELP is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Northern blotting with a ddx42-specific probe revealed an mRNA of ∼4 kb, which occurs in similar concentration in HeLa, Hep3B, COS, TC7 and HaCaT cells ( Figure 2B ). The coding sequence (cds) of the ddx42 mRNA was found by RT–PCR to be extended further 5′-ward than reported previously ( 41 , 49 ), resulting in a polypeptide consisting of 938 amino acids (compare Figure 2A ).…”
Section: Resultsmentioning
confidence: 56%
“…Northern blotting with a ddx42-specific probe revealed an mRNA of ∼4 kb, which occurs in similar concentration in HeLa, Hep3B, COS, TC7 and HaCaT cells ( Figure 2B ). The coding sequence (cds) of the ddx42 mRNA was found by RT–PCR to be extended further 5′-ward than reported previously ( 41 , 49 ), resulting in a polypeptide consisting of 938 amino acids (compare Figure 2A ).…”
Section: Resultsmentioning
confidence: 56%
“…Our work first identified three MYCT1 interacting proteins. All of them are related to RNA processing [20,24,25]. This might be one of the reasons that MYCT1 is able to recapitulate multiple c-MYC-related phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with their central roles in nucleic acid metabolic processes, an increasing number of helicases were found to be involved in severe diseases, often associated with significant cancer susceptibility. Autoantibodies to DEAD box protein have been reported in diabetes mellitus, 20 pancreatic cancer, 21 and connective tissue disease. 22 Our study demonstrated that autoantibodies to DEAD box polypeptide 3 were present in sera of patients with HCC.…”
Section: Discussionmentioning
confidence: 99%